CRYPTO HORIZON: THE DIGITAL KEY TO THE INVESTMENT FUTURE - DASHKO, Iryna; CHEREP, Oleksandr; MYKHAILICHENKO, Lubomir (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article comprehensively examines cryptocurrencies as a strategic tool for transforming the investment environment in the context of digitalization of the global economy. The current state of the crypto market is analyzed, key trends in its evolution are identified, and the role of digital assets in the formation of new investment models is characterized. Particular attention is paid to determining the investment potential of cryptocurrencies in the long term, taking into account such advantages as decentralization, market openness, technological innovation and accessibility. The author substantiates the concept of “crypto-horizon” - a new investment paradigm that combines a strategic vision of digital finance development with an understanding of the risks and prospects of cryptocurrencies. The author considers the importance of this concept in the formation of a new type of investor capable of operating in the digital economy, effectively managing risks and using innovative financial instruments. The paper also focuses on the key challenges of the crypto market: high volatility, legal uncertainty, information asymmetry, and limited financial literacy. The SWOT analysis made it possible to identify the strengths and weaknesses of crypto investing, as well as promising areas for the development of digital finance. The importance of state regulation, creation of a regulatory framework, development of digital finance infrastructure and raising public awareness in the field of investment is determined. The author emphasizes the need to form an effective regulatory framework for the integration of cryptocurrencies into the financial system. The role of public policy, educational initiatives, and infrastructure solutions in increasing confidence in digital assets is shown. It is substantiated that successful implementation of the “crypto-horizon” concept is possible only if there is a synergy of technology, regulation and investment culture. As a result, the authors conclude that cryptocurrencies are already playing the role of a digital key to the investment future, and their competent integration into national and international financial systems will be the key to the formation of an innovative, flexible and accessible investment ecosystem for the general population.